Practical patient management in reproductive medicine : evidence- and experience-based guidance - Cahill, David J. (Boca Raton, FL : CRC Press, 2020)
This text will provide doctors both in training and in practice with useful advice on managing women and men who are having trouble conceiving and couples with infertility and related disorders. Its combination of scientific information and practical advice for tackling problematic cases make this an accessible handy reference in outpatient clinics or in revision for professional exams, as well as a fully referenced information resource. Contents: Glossary of terms * Problems with puberty and its onset * Understanding infertility * Investigations in infertility * Influencing the sperm count * Helping women to ovulate * Damage to the uterus, the fallopian tubes and the ovaries * What to do if nothing wrong can be found and how to answer when a couple asks 'what can we do to improve our fertility?' *Assisted conception * Preserving fertility * Global perspectives on reproductive medicine * Reproductive biology in one other great ape (the gorilla) * Research questions still unanswered - And further reading
Glossary of terms. 1. Problems with puberty and its onset. 2. Understanding infertility. 3. Investigations in infertility. 4. Influencing the sperm count. 5. Helping women to ovulate. 6. Damage to the uterus, the fallopian tubes and the ovaries. 7. What to do if nothing wrong can be found and how to answer when a couple asks 'what can we do to improve our fertility?' 8. Assisted conception. 9. Preserving fertility. 10. Global perspectives on reproductive medicine. 11. Reproductive biology in one other great ape (the gorilla). 12. Research questions still unanswered - And further reading.
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / General; MEDICAL / Gynecology & Obstetrics; MEDICAL / Reproductive Medicine & Technology; Reproductive health; Reproductive health services -- Quality control